2021
DOI: 10.3390/w13020150
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Urbanization on Variations of Extreme Precipitation over the Yangtze River Delta

Abstract: The urbanization process is the hallmark of the population’s economic activities and land-use types, including population-, economic-, and landscape-urbanization. The question of how to classify the stations into urbanized and suburbanized stations is important for detecting the contribution rates of urbanization to precipitation extremes. This study used the fuzzy c-means clustering method to classify different urbanized level stations by population, economy, and impervious surface in the Suzhou-Wuxi-Changzho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Furthermore, deforestation and agricultural practices that involve removing natural vegetation cover can increase soil moisture loss and reduce the availability of water, leading to increased consecutive dry days. Urbanization can also impact CDD, as it can lead to increased surface runoff and reduced infiltration, which can decrease the amount of moisture in the soil and increase the number of consecutive dry days [51]. Prolonged CDD can lead to drought.…”
Section: Precipitation Duration-based Indicesmentioning
confidence: 99%
“…Furthermore, deforestation and agricultural practices that involve removing natural vegetation cover can increase soil moisture loss and reduce the availability of water, leading to increased consecutive dry days. Urbanization can also impact CDD, as it can lead to increased surface runoff and reduced infiltration, which can decrease the amount of moisture in the soil and increase the number of consecutive dry days [51]. Prolonged CDD can lead to drought.…”
Section: Precipitation Duration-based Indicesmentioning
confidence: 99%
“…In recent years, global climate change has impacted atmospheric circulation worldwide, while human activities represented by urbanization have exacerbated underlying surface in urban areas prominently, especially aggravating the extremeness and harmfulness of urban precipitation events [1][2][3]. With the rapid development of urbanization, the corresponding research on extreme precipitation in urban regions has been gradually increasing, which mainly has the following characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al analyzed the observation data of meteorological stations in Eastern China, finding that during 1955-2011, the heavy rainfall in both rural and urban stations increased significantly [35]. Kang et al analyzed the extreme precipitation index using meteorological observation data from 1980 to 2015, and the results show that the extreme precipitation intensity index of the SXCMA shows an upward trend, indicating that urbanization will increase extreme precipitation [43]. In recent years, increasing studies have shown that Lake Taihu and the surrounding SXCMA are experiencing increasing extreme precipitation events.…”
Section: Introductionmentioning
confidence: 99%